The contributions of C. F. Charter to tropical soil survey and classification - Borden, R. Wayne; Brammer, Hugh; Baillie, Ian C.; Hallett, Stephen (Elsevier, 2020)
Cecil Charter had taught botany and biology in China and Antigua for five years, when in 1931 he was engaged to conduct a soil survey of the sugarcane-growing areas of Antigua. This was followed by similar surveys elsewhere in the Caribbean. In 1944, he joined the West African Cacao Research Institute in the Gold Coast (now Ghana) to carry out soil investigations in the forest zones of West Africa. In 1949 he moved to organise the soil survey unit in the Gold Coast Department of Agriculture, and, in 1951, to found and direct the new Soil and Land Use Survey Department. He rapidly built up a highly professional unit that produced many practical and useful reports of high quality. He based the surveys on ecological principles, selecting river basins as mapping regions. In the initial absence of qualified soil scientists, he subdivided the soil survey process and trained school leavers as technicians for separate tasks. Teams of these technicians examined soils, vegetation and land use at regular intervals on regularly-spaced traverses cut across the topography. Charter’s contributions to soil science included his recognition of non-residual tropical soils formed in material brought to the surface by soil fauna and treefall. Also, he differentiated between highly acidic upland Oxysols in high-rainfall areas, which he considered unsuitable for cocoa cultivation, and less acidic Ochrosols, which were more suitable. Based on farmers’ experience and his ecological background, he differentiated between forest, thicket and savannah soils within these groups. He strongly advocated genetic and contextual classification of tropical soils.
Keywords: Charter; Gold Coast (Ghana); Team surveys; Non-residual soils; Genetic classification